Millennial-scale oscillations in the Kuroshio–Oyashio boundary during MIS 19 based on the radiolarian record from the Chiba composite section, central Japan - Takuya Itaki; Sakura Utsuki; Yuki Haneda; Kentaro Izumi; Yoshimi Kubota; Yusuke Suganuma; Makoto Okada (Progress in Earth and Planetary Science, 2022)
Abstract Marine isotope stage (MIS) 19 is considered to be the best orbital analog for the present interglacial. Consequently, clarifying the climatic features of this period can provide us with insights regarding a natural baseline for assessing future climate changes. A high-resolution radiolarian record from 800 to 750 ka (MIS 20 to MIS 18) was examined from the Chiba composite section (CbCS) of the Kokumoto Formation, including the Global Boundary Stratotype Section and Point for the lower–middle Pleistocene boundary on the Boso Peninsula on the Pacific side of central Japan. Millennial-scale oscillations in the Kuroshio warm and Oyashio cold currents were revealed by the Tr index, which is estimated using a simple equation based on radiolarian assemblages. The estimated Tr values ranged between 0.1 and 0.8 for MIS 18 through MIS 19, with minimum and maximum values corresponding to values observed off present day Aomori (41°N) and the Boso Peninsula (35°N), respectively. The observed patterns tended to be synchronous with the total radiolarian abundance associated with their production. Multiple maxima in radiolarian abundance occurred during periods of the Oyashio expanded mode before 785 ka and during periods of Kuroshio extension after 785 ka in MIS 19. Such increases in radiolarian abundance with the Kuroshio extension during MIS 19 are likely related to improvements in nutrient and photic environments with the development of a two-layer structure along the Kuroshio–Oyashio boundary zone. A similar pattern of millennial-scale climatic changes was also recognized in a precipitation record from the Sulmona Basin in central Italy, suggesting a close relationship with the CbCS record as a result of a large-scale climate system similar to the Arctic Oscillation in the northern hemisphere.